Peran Diskrepansi Karier Positif dalam Memprediksi Kesejahteraan Psikologis Mahasiswa dengan Efikasi Diri Sebagai Mediator - Maharani, Diva Aulia; Akmal, Sari Zakiah (Universitas Brawijaya, 2026)
Emerging adulthood is a developmental period during which university students face increasing academic and career-related responsibilities. These demands may contribute to uncertainty and reduced psychological well-being. This study examined the role of positive career discrepancy, defined as perceiving career progress as exceeding one’s goals, in predicting psychological well-being among university students, as well as the mediating role of academic self-efficacy. Participants were 159 undergraduate students (aged 18–25 years; M = 21.28, SD = 1.44) from public and private universities in Greater Jakarta, Indonesia, recruited through accidental sampling. Data were collected using the College Student Subjective Well-Being Questionnaire–Revised (CSSWQ-R), the Positive Career Goal Discrepancy Scale (PCGDS), and the Academic Self-Efficacy Scale (ASE). Simple mediation analysis showed that positive career discrepancy was positively associated with psychological well-being both directly (β = .18, p = .002) and indirectly through academic self-efficacy (β = .32, p < .001). These findings suggest that positive evaluations of career progress may enhance students’ psychological well-being by strengthening their academic self-efficacy. The study highlights the importance of fostering positive career perceptions and self-efficacy to support student well-being in higher education. Emerging adulthood merupakan periode perkembangan ketika mahasiswa menghadapi tuntutan akademik dan tanggung jawab karier yang semakin besar. Kondisi tersebut dapat menimbulkan ketidakpastian dan berdampak pada kesejahteraan psikologis. Penelitian ini bertujuan menguji peran diskrepansi karier positif, yaitu persepsi bahwa kemajuan karier telah melampaui target yang ditetapkan, dalam memprediksi kesejahteraan psikologis mahasiswa serta peran mediasi efikasi diri akademik. Partisipan penelitian adalah 159 mahasiswa sarjana berusia 18–25 tahun (M = 21.28, SD = 1.44) dari perguruan tinggi negeri dan swasta di Jabodetabek yang direkrut menggunakan teknik accidental sampling. Data dikumpulkan menggunakan College Student Subjective Well-Being Questionnaire–Revised (CSSWQ-R), Positive Career Goal Discrepancy Scale (PCGDS), dan Academic Self-Efficacy Scale (ASE). Hasil analisis mediasi sederhana menunjukkan bahwa diskrepansi karier positif berhubungan secara positif dengan kesejahteraan psikologis, baik secara langsung (β = .18, p = .002) maupun secara tidak langsung melalui efikasi diri akademik (β = .32, p < .001). Temuan ini menunjukkan bahwa persepsi positif terhadap kemajuan karier dapat meningkatkan kesejahteraan psikologis mahasiswa melalui penguatan efikasi diri akademik. Hasil penelitian menegaskan pentingnya pengembangan persepsi karier yang positif dan efikasi diri dalam mendukung kesejahteraan mahasiswa di lingkungan pendidikan tinggi.